The Dynamic Landscape of Canadian Philosophy: Three Views of Philosophical Reflection and Refutation. Issue 3 (3rd July 2021) - Hoff, Joan Whitman
ABSTRACT: Canadian philosophy has an intellectual history that highlights the importance of lived experience, reciprocity, and community. It fosters reflection on what it means to be human and what it means to be Canadian. The diversity of Canada moves one to engage in a dialectical process that is reflective and dynamic. It demands reconsideration of the views of traditional philosophies that are grounded in the objectivist, European tradition. Views are dynamic not only in relation to each other, but also in terms of their own development via the process of the dialectic. This article explores three examples of this. These include the philosophies of John Clark Murray, whose idealism and lived experience led to advocacy for the rights of workers and women, Chike Jeffers, whose work as an African Canadian philosopher led to an exploration of the role of African Canadian philosophers in the "academy, " and D'Arcy Rheault, who discusses his awakening to his Aboriginal identity and the significance of Anishinaabe philosophy.